Young people with disabilities and their sexual health: a descriptive review of needs, recommendations and interventions - Noëline Vivet; Elise de La Rochebrochard; Philippe Martin (BMC Public Health)
Abstract Background Worldwide, almost 180 million young people aged between 10 and 24 live with disability. They are often perceived as asexual, lacking in sexual desires, or as sexually inadequate. The sexual health of young people with disabilities thus remains a blind spot in health promotion. The aim of this descriptive review was to describe and analyze articles exploring needs, recommendations and interventions for promoting the sexual health (SH) of young people with disabilities. Methods We searched the PubMed and PsycINFO databases for international scientific articles on SH needs, recommendations or health promotion interventions for young people with disabilities (aged 10–24), published after 2013. Data were extracted using a standardized grid and analyzed quantitatively and qualitatively. Results Twenty-one articles were included, encompassing 13 SH interventions, 6 SH need studies, and 2 recommendations studies. Most studies were carried out in the United States (12/21), focusing on intellectual disability (6/21), with 7/21 studies involving parents. Among the needs studies, 2/6 explored the specific needs of young people, while the remaining 4 asked about their difficulties. None of the interventions were designed, co-constructed, or facilitated by young people with disabilities. Conclusion Very few studies have been done to understand the needs and to develop relevant interventions for promoting the sexual health of young people with disabilities. Research with rigorous methodologies is still required to better understand needs and to intervene as relevantly as possible. To this end, participatory research would be a valuable methodology, as it involves target audiences in the various stages of research. PROSPERO registration number PROSPERO 2023 CRD42023421365.